New and little known bees of the genus Sphecodes Latreille, 1804 (Hymenoptera: Apoidea: Halictidae) from Central Asia - Astafurova, Yulia V.; Proshchalykin, Maxim Yu.; Schwarz, Maximilian (Zootaxa, 2018)
Following a previously published study on Central Asian species of Sphecodes bees we here present a further report on 20 rarely recorded and little known species. This brings to 34 the number of species of Sphecodes known from this region, with two of them recorded for the first time: Sphecodes scabricollis Wesmael, 1835 and S. hakkariensis Warncke, 1992. Sphecodes sandykachis Astafurova & Proshchalykin, sp. n. is described from Turkmenistan and Uzbekistan. Sphecodes atlassa Warncke, 1992, stat. nov. and S. hakkariensis Warncke, 1992, stat. nov. are raised to full species level.